First-line treatment algorithm and guidelines in center-involving diabetic macular edema. Issue 6 (November 2019) - Kodjikian, Laurent; Bellocq, David; Bandello, Francesco; Loewenstein, Anat; Chakravarthy, Usha; Koh, Adrian; Augustin, Albert; de Smet, Marc D; Chhablani, Jay; Tufail, Adnan; García-Layana, Alfredo; Sudhalkar, Aditya; et al.
Management of center-involving diabetic macular edema represents a real therapeutic challenge. Diabetic macular edema is the leading cause of visual acuity impairment in diabetic patients. Since the advent of intravitreal drugs, management of diabetic macular edema has significantly evolved. The historical grid laser photocoagulation is no longer recommended as first-line treatment of diabetic macular edema owing to the findings of the pivotal randomized controlled trials, and anti-vascular endothelial growth factor therapy has emerged as first-line therapy. Steroids also represent a valid treatment option in the management of naïve diabetic macular edema and their efficacy has also been confirmed in several studies. The optimal treatment for diabetic macular edema should consider both general and ophthalmological comorbidities. Patient compliance and motivation should also be carefully evaluated as some treatments require monthly follow-up. Based on recent literature evidence, the present review provides clinicians with a first-line treatment algorithm for center-involving diabetic macular edema tailored to the patient's individual characteristics.